Isotretinoin and seizures: A narrative review - Muradov, Olga; Czar, Sarah (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Meadowlight Media, 2026)
Background: Isotretinoin, or 13-cis-retinoic acid, is a vitamin A derivative, that has been widely used to treat moderate-to-severe Acne vulgaris (On & Zeichner, 2013). An estimated 75%–95% of all teenagers suffer from acne (On & Zeichner, 2013). Isotretinoin is considered effective, safe, and has been superior to other therapies for acne lesion counts (Vallerand et al., 2018). Several adverse events are described in the literature, most commonly dermatological (Vallerand et al., 2018). Neuropsychiatric and gastrointestinal side effects have been noted (Bremner, 2021; Kontaxakis et al., 2009; On & Zeichner, 2013; Vallerand et al., 2018) and a range of neurological symptoms have also been documented in case reports (Bremner, 2021), including headaches, pseudotumor cerebri, also referred to as idiopathic intracranial hypertension (IIH), and generalized encephalopathy in association with isotretinoin use. Seizures linked with isotretinoin are only present in the literature in the form of case studies, but may remain both under-recognized by clinicians and patients and subsequently under-reported.Methods: A narrative literature review was conducted to identify all published clinical studies involving patients who use isotretinoin and de novo seizures, from Pubmed, MEDLINE, Embase, and Summons for KRS, yielding 35 relevant publication titles and abstracts. Two additional relevant studies were discovered through manual search of reference lists of included studies. After excluding non-related publications, 26 publications underwent full-text review and 21 of these studies were found to not specifically address seizures and oral isotretinoin use. Reporting of results was guided by the Preferred Reporting Items for Systematic Reviews and Meta Analyses Extension for Scoping Reviews (PRISMA-ScR; Appendix A).Results: Data were organized into the following themes in the literature: reported seizure occurrence in patients using isotretinoin, associated ocular abnormalities, proposed pathophysiology mechanisms, and patient outcomes.Conclusion: Case reports in the literature suggest a potential association between isotretinoin use and seizures. Clinician vigilance is essential in properly identifying isotretinoin use in patients presenting to emergency services with seizures. Early recognition impacts patient care both in-hospital and at post-discharge follow-up.